If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(x+2)=4(x+1)
We move all terms to the left:
-(x+2)-(4(x+1))=0
We get rid of parentheses
-x-(4(x+1))-2=0
We calculate terms in parentheses: -(4(x+1)), so:We add all the numbers together, and all the variables
4(x+1)
We multiply parentheses
4x+4
Back to the equation:
-(4x+4)
-1x-(4x+4)-2=0
We get rid of parentheses
-1x-4x-4-2=0
We add all the numbers together, and all the variables
-5x-6=0
We move all terms containing x to the left, all other terms to the right
-5x=6
x=6/-5
x=-1+1/5
| 9/p-10=2/4+p | | 28=x+164 | | -6(1+v)=2(1+-3v)+-8 | | G(0)=x*2+3 | | 3n+20=4n-7 | | b-6/3=1 | | 6=-5(c+4)=10 | | –8=u−42/–7 | | d+1/2=-2 | | 6p+10=-56 | | 62=12x+10 | | G(-2)=x*2+3 | | −8.5x+0.22=−3.18 | | 3(x-6)-8x=-2+5(2+5(2x1) | | 56=12x+10 | | -39+3a=(2a-8) | | y+6/3=-4 | | 51=3(t-56) | | 8^x/5=23 | | 3x/7-x/5=2/35 | | 3n+2n-1=2 | | |-8x+20|=|2x+40| | | 12x-5-3x=+35 | | G(3)=x*2+3 | | 7x²+3x-10=0 | | 36=t/8+33 | | 24=n/2+20 | | 18=3(p-10) | | 59=12x+10 | | 4r^2-8r=-12 | | 7y-8=22 | | F(5)=-2x+15 |